A Note on the Status of Lac Insect Natural Enemies in Arid Western Plains of India - Kalahal, Chetan; Swami, Hemant; ., Lekha (Indian Journal of Plant Protection, 2020)
The investigations on natural enemies (major predator and parasitoids) of lac insect were carried out in the lac insect museum cum laboratory situated at Department of Entomology, Rajasthan College of Agriculture, MPUAT, Udaipur during Katki season 2016 with an aim to record the natural enemies of lac insect. The results reveal that the three species of hymenopteran parasitoids viz., Erencyrtus dewitzi Mahd (88.4%) and Tachardiaephagus tachardiae Howard (5.2%) belonging to family Encyrtidae and Aprostocetus (Tetrastichus) purpureus Cameron (4.2%) belonging to family Eulophidae contributed (97.8%) to the total natural enemies population and two species of Lepidopteran predators viz., Eublemma amabilis (0.70%) belonging to family Noctuidae and Pseudohypatopa (Holcocera) pulverea Meyr (0.3%) belonging to family Blastobasidae contributed 1 per cent to the total natural enemies population and one species of Coleopteran predator i.e. Oryzaephilus spp belonging to family Silvanidae contributed 1.3 per cent to the total natural enemies population.